Human mesenchymal stem cells: From immunophenotyping by flow cytometry to clinical applications - Nery, Arthur A.; Nascimento, Isis C.; Glaser, Talita; Bassaneze, Vinicius; Krieger, José E.; Ulrich, Henning (Cytometry. Part A, 2013)
Modern medicine will unequivocally include regenerative medicine as a major breakthrough in the re‐establishment of damaged or lost tissues due to degenerative diseases or injury. In this scenario, millions of patients worldwide can have their quality of life improved by stem cell implantation coupled with endogenous secretion or administration of survival and differentiation promoting factors. Large efforts, relying mostly on flow cytometry and imaging techniques, have been put into cell isolation, immunophenotyping, and studies of differentiation properties of stem cells of diverse origins. Mesenchymal stem cells (MSCs) are particularly relevant for therapy due to their simplicity of isolation. A minimal phenotypic pattern for the identification of MSCs cells requires them to be immunopositive for CD73, CD90, and CD105 expression, while being negative for CD34, CD45, and HLA‐DR and other surface markers. MSCs identified by their cell surface marker expression pattern can be readily purified from patient's bone marrow and adipose tissues. Following expansion and/or predifferentiation into a desired tissue type, stem cells can be reimplanted for tissue repair in the same patient, virtually eliminating rejection problems. Transplantation of MSCs is subject of almost 200 clinical trials to cure and treat a very broad range of conditions, including bone, heart, and neurodegenerative diseases. Immediate or medium term improvements of clinical symptoms have been reported as results of many clinical studies. © 2012 International Society for Advancement of Cytometry